Penerapan Metoda Job Safety Analysis Dalam Identifikasi Potensi Bahaya Pada Pekerja Divisi Pipa, Sumatera Barat - Nailul Hikmi; Ridwan Firwandri; Budi Haryanto (POLTEKKES KEMENKES MANADO, 2020)
Number of work accidents in Kab. Padang Pariaman, West Sumatra in 2012 there were 837 cases of work accidents, in 2013 it increased to 903 cases, in 2014 there were 1050 cases, in 2015 there were a decrease in cases to 956 cases, in 2016 there was an increase in work accident cases to 1535 cases. This study aims to find and prevent potential hazards by identifying hazards, assessing and controlling risks to workers. This study used the JSA method with univariate analysis. The study population was 155 workers with a sample of 112 respondents. This study uses the Jobs Safety Analysis (JSA) sheet by means of observation and interviews and then presents the results of the analysis of the checklist and questionnaire in tabular form. There are two stages of high-risk work with a score of 20 (16-24) in the uncoiling section, two stages of high-risk work with a score of 20 (16-24) in the accumulating section, three high-risk stages with a score of 16 (16-24) in the forming section and sizing, four high-risk stages with a score of 16 (16-24) on the packing section. Risk control is carried out at high risks that produce a large enough impact. It is hoped that the company should carry out risk control in the form of engineering by assembling machines that are safe, productive and efficient.